2006
DOI: 10.5194/angeo-24-3481-2006
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of magnetic dipolarization for sawtooth events and isolated substorms at geosynchronous orbit with GOES data

Abstract: Abstract. We investigate whether the dipolarization process during sawtooth events is global or not through an examination of the local time distribution of the magnetic tilt angle (i.e. the angle between the B vector and the equatorial plane in dipole VDH coordinates) at geostationary orbit. From the statistical analysis of 207 individual teeth and 212 isolated substorms, we find that individual teeth follow a dipolarization pattern similar to that observed for isolated substorms. The dipolarization for indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 18 publications
9
34
0
Order By: Relevance
“…When the proton flux injections are binned according to MLT the earliest injection appears to be in the 22-01 MLT bin. This sector is similar to the location of dipolarization observed by the GOES geosynchronous spacecraft (Cai et al, 2006) and the magnetic field line mapped location of the auroral onset observed with Viking auroral images (Elphinestone et al, 1991). Our location of the proton injection, however, is duskward of the mean location determined from the Polar ENA images of seven isolated substorm injections (Reeves and Henderson, 2001).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…When the proton flux injections are binned according to MLT the earliest injection appears to be in the 22-01 MLT bin. This sector is similar to the location of dipolarization observed by the GOES geosynchronous spacecraft (Cai et al, 2006) and the magnetic field line mapped location of the auroral onset observed with Viking auroral images (Elphinestone et al, 1991). Our location of the proton injection, however, is duskward of the mean location determined from the Polar ENA images of seven isolated substorm injections (Reeves and Henderson, 2001).…”
Section: Discussionsupporting
confidence: 63%
“…Liou et al (1999Liou et al ( , 2000Liou et al ( , 2002 found that 65% of the Pi 2 pulsations begin about 0-3 min after the start of the auroral breakup identified with the Polar ultraviolet images, while the GOES satellites observed dipolarizations 1.772.7 min after this time. The most probable location of the geosynchronous location of this dipolarization was found to be about 23 MLT (Cai et al, 2006). When the Pi 2 pulsations were compared with the standard AL index, Hsu and McPherron (2003) and Hsu and McPherron (2007) indicate that there is no clear relationship between the start of the Pi 2 pulsations and the AL index.…”
Section: Introductionmentioning
confidence: 91%
“…However, during the expansion phase of certain substorm activities, including the category we discuss in this paper (see e.g. Cai et al, 2006;Henderson et al, 2006;and Andalsvik et al, 2011), the WEJ and the Harang reversal boundary expand westward across the 18:00 MLT meridian (Andalsvik et al, 2011), as we shall also demonstrate below. According to Nielsen and Greenwald (1979) the Harang discontinuity (our Harang reversal boundary) tended to be observed by the Stare radar in the 21:00-24:00 MLT sector, but it was observed as early as 18:30 MLT under very disturbed conditions.…”
Section: P E Sandholt Et Al: Repetitive Substorm Activity Driven Bmentioning
confidence: 99%
“…Based on a statistical study with GOES data, Cai et al (2006) argued that the dipolarisation is seen from 16 h to 4 h MLT, and the initiation is in the sector between 22 h and 0 h MLT. Kitamura et al (2005) deduced the substorm current wedge (SCW) of a full width (at full maximum) of ∟12 h in MLT from ground-based magnetometer data.…”
mentioning
confidence: 99%